Histomorphological effects of valproic acid on the development of pancreatic islets in chick - Akhtar, Lubna; Rashid, Nadia; Haider , Syed Muhammad Aleem; Haider , Syed Zulifqar; Jamshed , Nausheen; Shafi Minhas, Ruqqia (ADVANCES IN BASIC MEDICAL SCIENCES, 2026)
Objective: To determine the developmental histo-morphological effects of valproic acid on pancreatic islets by comparing the pancreatic islets of freshly hatched chicks with the pancreatic islets of chicks not receiving this medication intervention. Study design: Experimental study. Place and Duration of Study: At department of anatomy CPSP, Regional Centre, Islamabad, extending from February till November 2010. Methodology: Two groups were made with thirty fertilized chicken eggs each, Group-A (experimental) and Group-B (control). Prior to incubation, Group-A's eggs were injected with valproic acid. Group-B eggs received a sham treatment using regular saline in same volume. On hatching, pancreata were removed and stained with Eosin and hematoxylin, orange G-light green and aldehyde fuchsin stain. The number of islets and the cells that make them, as well as the area of islets lobe-wise in the pancreatic splenic and third lobes were measured in each section. After statistical analysis, the collected data was contrasted with the control groups. Results: The histo-morphological findings demonstrated that valproic acid inhibited the Pancreatic islets development in completely hatched chicks, resulting in a reduction in the quantity and area of the islets as well as in the number of component cells. Conclusion: The formation of pancreatic islets and the cells that make them up is intensely suppressed by VPA. It causes hypotrophy and islet hypoplasia in newborns. Key words: Pancreatic, valproic acid, chick embryo.